Netrophil-Lymphocyte Ratio (NLR) as a Predictor of Severity in Covid-19 Patients - Fasni Halil; Marwah Widuri Anwar; Sundari Sundari (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Early identification is needed to predict the condition of patients who are at risk of worsening symptoms to become more severe. Simple laboratory tests such as measurement of the neutrophil-lymphocyte ratio are known to be used as factors to determine the patient's prognosis in various clinical situations. The purpose of this study was to analyze the value of the neutrophil-lymphocyte ratio as a predictor factor for COVID-19. This study is retrospective, using medical record data of 327 Covid-19 patients at the Dr Chasan Boesoirie Hospital Ternate from April to September 2021. Subjects were classified as not severe and severe COVID-19. The value of the neutrophil-lymphocyte ratio was determined based on the results of a routine blood test (sysmex XN-1000B3 BF). Data were analyzed using SPSS version 16, Pearson's test to determine the relationship between NLR and severity and using the ROC (Receiver Operating Characteristic) curve to determine the strength of the relationship with the Cut-off value, p < 0.05 and AUC to determine the sensitivity and specificity of NLR to COVID-19 severity. Results: From 327 subjects consisting of 229 non-severe and 98 severe, the neutrophil-lymphocyte ratio (NLR) in the non-severe (3.45±2.02) was significantly different from the severe (9.73±5.64) (p < 0.00). The ROC (Receiver operating Characteristic) curve shows that the NLR has a sensitivity of 83%, specificity of 82% with a cut-off of 3.5 with a positive predictive value (PPV) of 88.2% and a negative predictive value (NPV) of 83.6%. The results of this study can be used as a reference for determining clinical prognosis using neutrophil ratio data.